2007
DOI: 10.1590/s1516-89132007000400019
|View full text |Cite
|
Sign up to set email alerts
|

Penicillium expansum versus antagonist yeasts and patulin degradation in vitro

Abstract: Taking into account the preliminary antagonistic/biodegradation property showed by Pichia membranifaciens and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 35 publications
0
44
0
3
Order By: Relevance
“…In the last decade, a few studies investigated the effect on patulin accumulation by BCAs that are effective against P. expansum. Pichia ohmeri (11), Candida sake and Pantoea agglomerans (12), and several Lactobacillus species (13) were able to reduce patulin accumulation in vitro. These studies excluded the metabolism of patulin by these microorganisms, and the observed reduction was attributed to the protection of fruits from infection by patulin-producing P. expansum and/or to the decrease of mycotoxin production.…”
mentioning
confidence: 98%
“…In the last decade, a few studies investigated the effect on patulin accumulation by BCAs that are effective against P. expansum. Pichia ohmeri (11), Candida sake and Pantoea agglomerans (12), and several Lactobacillus species (13) were able to reduce patulin accumulation in vitro. These studies excluded the metabolism of patulin by these microorganisms, and the observed reduction was attributed to the protection of fruits from infection by patulin-producing P. expansum and/or to the decrease of mycotoxin production.…”
mentioning
confidence: 98%
“…Walker et al (1995) reported the susceptibility of yeast and filamentous fungi caused by the killer positive strains of S. cerevisiae, P. anomala and Williopsis mrakii. Studies by Coelho et al (2006Coelho et al ( , 2007 showed 58.15% inhibition of spore germination of P. expansum with supernatant of C. guilliermondii cultivate obtained after 72 h of incubation at 25 o C, whereas Pichia ohmeri (25 o C/48 h) inhibited the hyphal length development in 64.37%, both associated with the killer factor. Although there had not been any reports on the action of killer toxins produced by Kluyveromyces sp.…”
Section: Antifungal Assaymentioning
confidence: 95%
“…The antifungal assay in solid medium was used for screening the yeasts with potential activity against the fungal strains. This method allowed observing two types of inhibition, i.e., competition for the nutrients, identified by yeast growth pumping through the edge of the well and/or extra-cellular compound production by antibiosis, characterized by the inhibition zone with no growth of spoilage mould (Coelho et al 2007). …”
Section: Antifungal Assay In Solid Mediummentioning
confidence: 99%
“…Métodos alternativos são desenvolvidos para o controle do bolor azul como a utilização de microrganismos antagônicos (COELHO et al, 2007;LEVY et al, 2000) As leveduras e seus metabólitos também vêm sendo estudados para utilização no controle biológico. Levy et al (2000) analisaram o potencial antagônico de 18 leveduras contra Penicillium spp produtor de patulina, avaliando o potencial e a estabilidade dos compostos ativos produzidos, utilizando o sobrenadante do meio de leveduras para realização de antibiograma.…”
Section: Dombrink-kurtzman E Blackburnunclassified
“…Ao considerar o efeito antagônico e degradador de Pichia membranifaciens e Sporobolomyces roseus na degradação de 588,4 para 290,0 µg de patulina (25ºC/15 dias) em estudos preliminares (COELHO et al, 2004;LEVY et al, 2002), Coelho et al (2007) avaliaram o efeito degradador de Pichia ohmeri 158 isolada de ecossistema natural (formigueiro) sobre toxina produzida por P. expansum toxigênico (107 µg/mL). Para tanto, foi adicionado simultaneamente 223 µg de patulina e 3,0 x 10 6 células de P. ohmeri 158 em 25 mL de Caldo Extrato de Malte, seguido de quantificação aos 2, 5, 10 e 15 dias de incubação a 25ºC por Cromatografia Líquida de Alta Eficiência.…”
Section: Lai Fuh E Shihunclassified